Perceived burden in dealing with different rare diseases: a qualitative focus group study - Bernd Löwe; Natalie Uhlenbusch; Miriam K Depping (BMJ Open)
Objectives There are more than 6000 heterogeneous rare diseases and little is known about shared experiences of affected individuals in everyday life and healthcare. Objective of this study was to explore perceived burden of patients with rare chronic diseases and identify commonalities and differences in the experiences of patients with four heterogeneous conditions.Design A qualitative focus group study.Setting In four separate and diagnostically homogeneous focus groups, we asked patients about the perceived burden of living with their rare disease. The focus groups took place at a university medical centre in Germany.Participants Individuals with neurofibromatosis type 1 (n=4), primary sclerosing cholangitis (n=5), pulmonary arterial hypertension (n=4) and Marfan syndrome (n=5).Results We identified five main themes: medical problems, psychological burden, problems with the healthcare system, constraints and interpersonal problems. While medical problems differed widely between the diagnostic groups, patients with different conditions independently reported many common problems including psychological burden, constraints in professional, personal and daily life, stigmatisation and others lacking understanding. Shared problems pertaining to the healthcare system seem related to the rarity of the conditions (eg, limited access to adequate care, lack of knowledge).Conclusions Despite clinical heterogeneity of rare diseases, affected individuals have many common experiences. Some of these experiences may resemble the burden of living with a chronic disease. However, patients reported aspects, which seem to be specific for rare chronic diseases. Generic interventions targeting shared burdens among patients with different diseases could provide adequate treatment in light of finite healthcare resources.